Immune Response Of Hepatitis C Virus Infected Patients, Jazan Region, Saudi Arabia (Journal of Namibian Studies : History Politics Culture, 2024)
CD4 T cells are essential for coordinating the immune response and providing help to other immune cells, while CD8 T cells are responsible for directly eliminating virus-infected cells. The interplay between CD4 and CD8 T cells is crucial for an effective immune response. A hospital-based prospective study on 40 hepatitis HCV patients in Jazan region to assess the host immune response was conducted and analyzed. The results indicate a significant decrease in both CD4 and CD8 cell counts following HCV infection. The moderate positive correlation observed between CD4 counts pre and post-infection suggests that higher CD4 counts prior to infection may contribute to relatively higher CD4 counts during the post-infection stage. However, no significant correlation was found between CD8 counts pre and post-infection. These findings highlight the impact of HCV infection on the patient's immune response and the potential importance of CD4 T cells in the immune response against HCV. The current studies examining the counts of CD4 T and CD8 T cells in 40 patients have indicated the significance of these HCV-specific T cells in the immune response against HCV. Although, the findings obtained suggest that the timing and coordination of the expansion of these T cell responses during primary and chronic HCV infection could influence the effectiveness of controlling the initial infection. Further research and analysis are needed to fully understand the impact of HCV infection on T cell populations and their functional characteristics.